2014
DOI: 10.1002/cphc.201402234
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐Charge Differentiation of Streptavidin and Avidin by Atomic Force Microscopy–Force Spectroscopy

Abstract: Chemical information can be obtained by using atomic force microscopy (AFM) and force spectroscopy (FS) with atomic or molecular resolution, even in liquid media. The aim of this paper is to demonstrate that single molecules of avidin and streptavidin anchored to a biotinylated bilayer can be differentiated by using AFM, even though AFM topographical images of the two proteins are remarkably alike. At physiological pH, the basic glycoprotein avidin is positively charged, whereas streptavidin is a neutral prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 60 publications
3
26
1
1
Order By: Relevance
“…These estimates are consistent with the results obtained from STM images. Numerous reports have shown that protein hydration and tip radius artifacts affect solution-based STM and AFM images [34,35,49,50]. Although we successfully resolved sub-molecular features, greater molecule size reflected is a limitation of our method.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…These estimates are consistent with the results obtained from STM images. Numerous reports have shown that protein hydration and tip radius artifacts affect solution-based STM and AFM images [34,35,49,50]. Although we successfully resolved sub-molecular features, greater molecule size reflected is a limitation of our method.…”
Section: Discussioncontrasting
confidence: 58%
“…Its crystal structure was determined by multi-wavelength anomalous diffraction [33]. Streptavidin images obtained using scanning probe microscopes appear as round spots without sub-molecular details [34][35][36][37]. Figure 2(a) shows an STM image of streptavidin molecules that resembles the crystal structure, but are not identical.…”
Section: Sub-molecular Features Observed On Streptavidin and Antibodymentioning
confidence: 99%
“…The pI of surfacebound streptavidin has been measured using Surface Force Apparatus (SFA) and Atomic Force Microscopy which demonstrated a pI of 5.0 ± 0.5. 79,83 Experimental determination of streptavidin pI is discussed further in ESI section 4. † Other biomolecules.…”
Section: Streptavidin Biochemistrymentioning
confidence: 99%
“…Additionally, using these techniques it is difficult to assess the properties of functional viral particles in physiological conditions. The density of charge of other biomolecules, such as single dsDNA molecules 13 , supported lipid bilayers 14 , and the avidin-streptavidin system 15 have also been measured. The subsequent refinement of this technique allowed the measurement of the electrical charge of biomolecules forming monolayers, such as purple membrane 12 resulting in a density of charge of -0.312 e 0 /nm 2 , where e 0 is the absolute value of the electron charge (1 C/m 2 = 6.24e 0 /nm 2 ).…”
Section: Introductionmentioning
confidence: 99%